Behavioral changes during dental appointments in children having tooth extractions - Mariana Gonzalez Cademartori; Priscila Martins; Ana Regina Romano; Marília Leao Goettems (Wolters Kluwer Medknow Publications, 2017)
Background: Tooth extractions are associated with anxiety-related situations that can cause behavioral problems in pediatric dental clinics. Aim: We aimed to describe the behavior of children during tooth extraction appointments, compare it to their behavior in preceding and subsequent dental appointments, and assess the behavioral differences according to gender, age, type of dentition, and reason for extraction. Settings and Design: This was a retrospective study based on information obtained from records of children between 6 and 13 years of age who were cared for at the Dentistry School in Pelotas, Brazil. Materials and Methods: Child behavior was assessed during the dental appointment that preceded the tooth extraction, during the tooth extraction appointment, and in the subsequent dental appointment using the Venham Behavior Rating Scale. Statistical Analysis: Results were analyzed using the Pearson Chi-square and McNemar tests. Results: Eighty-nine children were included. Cooperative behavior prevailed in all the dental appointments. The prevalence of "mild/intense protest" was higher in the tooth extraction appointments than in the previous or subsequent dental appointments (P < 0.001). No significant differences in behavior were detected between the type of dentition (primary or permanent teeth), reason for extraction or gender. Conclusion: In this sample of children treated at a dental school, the occurrence of uncooperative behavior was higher during the tooth extraction appointments than in the preceding and subsequent dental appointments.